Endovascular management of primary long-segment inferior vena cava occlusion: treatment strategies and clinical outcomes - Jiang, Jianjun; Li, Mingli; Li, Guangzhen; Liu, Yang; Su, Qingbo (Frontiers in Pharmacology, 2025)
BackgroundPrimary long-segment occlusion of the inferior vena cava (IVC) is a rare condition with diverse clinical presentations. The optimal management approach for this condition remains uncertain, warranting further investigation into endovascular treatment methods.MethodsA retrospective study conducted at Qilu Hospital of Shandong University from 2012 to 2018 assessed 16 patients with primary long-segment IVC occlusion. Patients underwent comprehensive imaging evaluations and received endovascular interventions such as angioplasty, stent placement, and online blood flow restoration. Additionally, a literature review was performed to analyze current practices in managing IVC occlusion.ResultsEndovascular treatment was completed in all patients, with favorable primary and secondary patency rates during follow-up. Clinical symptoms significantly improved post-treatment, and the majority of patients achieved IVC patency without major complications. The study showcased the efficacy of angioplasty and stent placement in managing primary IVC occlusion.ConclusionEndovascular therapy is a safe and effective approach for tackling long-segment IVC occlusion, leading to improved patient outcomes. Long-term anticoagulant prophylaxis is advised to mitigate the risk of venous thrombosis in these patients. This study contributes valuable insights for guiding clinical practice in treating primary IVC occlusion.